STUDI PERBANDINGAN PENGARUH BERBAGAI WARNA LAMPU DAN BUNYI TERHADAP PERTUMBUHAN SAYURAN SAWI HIJAU (BRASSICA RAPA VAR. PARACHINENSIS L) - Musdarina, Musdarina; Hernawati, Hernawati; Fitriyanti, Fitriyanti (Universitas Islam Negeri Alauddin Makassar, 2019)
Research has been conducted which aims to determine the effect of various colors of LED light and sound effects with frequency of 280Hz-16KHz. This research was conducted by seeding mustard greens for 2 weeks then moving mustard greens to polybags by giving two treatments. First treatment of mustard greens illuminated by LED lights with the color red, yellow, green and the fourth polybag left without the addition of LED light. The second treatment is every 1 polybag of green mustard illuminated by LED lights with red, yellow, green lights at night for 4 hours then exposed to sound in the morning for 4 hours and the fourth polybag is exposed to sound without the addition of lights. The results of this study indicate the effect of the addition of red LED light color on the plant is clearly seen in the width of green mustard leaves that have wider leaves between the addition of other LED light colors and the number of leaves produced more than the addition of yellow, green and without additional light. The effect of exposure to sound on the plant has a fairly good influence on the height of the stem, stem width and number of leaves compared to plants that are not given sound exposure and in plants that are given additional LED light then the sound produces better plant growth compared to plants that only given additional lights or just given a sound.